The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.5005/jp-journals-10071-23965
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Care in India in 2018–2019: The Second Indian Intensive Care Case Mix and Practice Patterns Study

Abstract: A bstract Background We aimed to study organizational aspects, case mix, and practices in Indian intensive care units (ICUs) from 2018 to 2019, following the Indian Intensive Care Case Mix and Practice Patterns Study (INDICAPS) of 2010–2011. Methods An observational, 4-day point prevalence study was performed between 2018 and 2019. ICU, patient characteristics, and interventions were recorded for 24 hours, and ICU outcomes till 30 days after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Left against medical advice and DAMA decisions have been previously reported in Indian studies. 6 , 9 Slow code or sham CPR is sometimes performed in non-salvageable situations, causing ethical distress to HCPs. 53 Informed non-dissent may be an ethical alternative to slow code.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Left against medical advice and DAMA decisions have been previously reported in Indian studies. 6 , 9 Slow code or sham CPR is sometimes performed in non-salvageable situations, causing ethical distress to HCPs. 53 Informed non-dissent may be an ethical alternative to slow code.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Most of the limitations of support decisions in India culminated in a terminal discharge against medical advice (DAMA) or left against medical advice (LAMA), as suggested by the point prevalence Indian study INDICAPS II. 9 …”
Section: Introductionmentioning
confidence: 99%
“…This data contradicts western literature which favors a closed ICU structure in order to achieve better outcomes. On the contrary, the INDICAPS-II 4 study indicated that having a closed ICU structure was an independent predictor of mortality, wherein the closed ICU was defined as one in which, only the ICU team doctors wrote the final orders for the patient. A third model, the hybrid model or mandatory consult model is in which all patients admitted to the ICU are seen by the primary consultant and the ICU team, with both having the privilege to write orders.…”
Section: R Ole Of I Ntensive C ...mentioning
confidence: 99%
“…CO and SVV monitoring remained low even in this second survey which happened after a gap of ~8 years. 6 …”
Section: Introductionmentioning
confidence: 99%